Prevalence and characteristics associated with default of treatment and follow‐up in patients with cancer. (24th March 2015) - Chan, C.M.H.; Wan Ahmad, W.A.; Md Yusof, M.; Ho, G.F.; Krupat, E.
<x xml:space="preserve">Abstract</x> Defaulting is an important issue across all medical specialties, but much more so in cancer as delayed or incomplete treatment has been shown to result in worse clinical outcomes such as treatment resistance, disease progression as well as lower survival. Our objective was to identify psychosocial variables and characteristics associated with default among cancer patients. A total of 467 consecutive adult cancer patients attending the oncology clinic at a single academic medical centre completed the Hospital Anxiety and Depression Scale and reported their preference for psychological support at baseline, 4–6 weeks and 12–18 months follow‐up. Default was defined as refusal, delay or discontinuation of treatment or visit, despite the ability to do so. A total of 159 of 467 (34.0%) cancer patients were defaulters. Of these 159 defaulters, 89 (56.0%) desired psychological support, compared to only 13 (4.2%) of 308 non‐defaulters. Using a logistic regression, patients who were defaulters had 52 times higher odds (P = 0.001; 95% confidence interval 20.61–134.47) of desiring psychological support than non‐defaulters after adjusting for covariates. These findings suggest that defaulters should be offered psychological support which may increase cancer treatment acceptance rates and improve survival.